Determinants of the Intention to Use Performance-Enhancing Substances Among Portuguese Gym Users - Tavares, Ana Sofia R.; Rosado, António Fernando; Marôco, João; Calmeiro, Luis; Serpa, Sidonio (Frontiers in Psychology, 2020)
The purpose of this study is to examine the determinants of the intentions to use prohibited performance-enhancing substances (PES) and to test the Theory of Planned Behavior’s usefulness in predicting self-reported PES use in both genders. A convenience sample of Portuguese gym users (n = 453) completed an anonymous web-based survey. Structural equation modeling, multigroup analysis, and t-test with the Welch correction for heterokedastic variances were used. At the structural level, results support attitudes, beliefs, and subjective norms in predicting intentions to PES use in gym users, with subjective norms being its strongest predictor. Moreover, results showed a significant association between self-reported PES use and intentions to use. The predictive model was invariant across genders; however, compared to males, females believed less in the performance-enhancing effects of PES, were less prone to the influence of significant others, and had weaker intentions to use these substances. Psychological strategies should be based on subjective norms, alongside beliefs and attitudes, toward PES use as these variables influence the intention to use PES in this particular population.